(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The data about current species composition, structure and spatial distribution of macrophytobenthos in Tendrivska and Yagorlycka Bays (Black Sea) are given. 46 macrophytes species have ben found. Red algae is a more numerous group of the macrophytes. 5 plant associations were identify in the macrophytobenthos structure. Quantitative assessment of the macrophytobenthos current state has shown a significant reduction in its average biomass compared to literature data.